2014
DOI: 10.1002/chem.201304957
|View full text |Cite
|
Sign up to set email alerts
|

m‐Metallaphenol: Synthesis and Reactivity Studies

Abstract: Treatment of the osmium complex [Os{CHC-(PPh3 )CH(OH)-η(2) -C≡CH}(PPh3 )2 (NCS)2 ] (1) with excess triethylamine produces the first m-metallaphenol complex [Os{CHC(PPh3 )CHC(OH)CH}(PPh3 )2 (NCS)2 ] (2). The NMR spectroscopic and structural data as well as the nucleus-independent chemical-shift (NICS) values suggest that osmaphenol 2 has aromatic character. The reactivity studies demonstrate that 2 can react with different isocyanates to form the annulation reaction products [Os{CHC(PPh3 )CHC(OCONR)C}(PPh3 )2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 58 publications
1
24
0
Order By: Relevance
“…[4e] Various metallacycles that contain one or two main-group heteroatoms have been isolated,s uch as metallapyridines, [6k, 14] metallapyridynes, [6k] metallathiobenzenes, [15] metallabenzothiophenes, [16] metallabenzofurans, [17] metallabenzothiazoles, [6j, 18] metallabenzoxazoles, [18] metallabenzoxathialoes, [19] and metallabenzoxolones. [20] This strategy significantly enriches the structurala nd compositional varieties of metallacycles.…”
Section: Introductionmentioning
confidence: 99%
“…[4e] Various metallacycles that contain one or two main-group heteroatoms have been isolated,s uch as metallapyridines, [6k, 14] metallapyridynes, [6k] metallathiobenzenes, [15] metallabenzothiophenes, [16] metallabenzofurans, [17] metallabenzothiazoles, [6j, 18] metallabenzoxazoles, [18] metallabenzoxathialoes, [19] and metallabenzoxolones. [20] This strategy significantly enriches the structurala nd compositional varieties of metallacycles.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang, Xia and co-workers prepared and characterised an osmaphenol complex (in which osmium is part of the aromatic ring) bearing a triphenylphosphonium group. 13 The use of phosphonium groups in the preparation of this class of organometallic compound is very common as observed in a recent review by Cao et al 14 Dimé et al reported that controlled potential electrolysis of a triarylmesosubstituted Ni(II) porphyrin in the presence of triphenylphosphine as a nucleophile allowed the electrochemical synthesis of the corresponding phosphonium derivative. 15 Polymeric organometallic materials were also described.…”
Section: Synthesis and Characterisationmentioning
confidence: 99%
“…Hydroxyl group substituted osmabenzene, that is, m ‐osmaphenol can also perform similar S N Ar reactions. By treatment of different isocyanates with m ‐osmaphenol, a series of osmabenzenes with urethane linkages could be generated . The following intramolecular S N Ar reaction by urethane linkages in the presence of bases afforded a series of annulation products.…”
Section: Reactions With Nucleophilesmentioning
confidence: 99%